75.7k views
0 votes
Solve for x and write your answer in simplest form: -(6/5x + 6) + 2 = -4/5(-5x + 7)

2 Answers

0 votes

Answer:

4/13

Explanation:

-6/5x - 6 + 2=4x - 28/5

-6/5x - 4=4x - 28/5

-6/5x - 4x= -28/5 + 4 (multiply each side by 5)

-6x - 20x= -28+20

-26x= -8 (divide each side by 26)

-x= -8/26 (multiply each side by -1)

x= 8/26 (reduce)

x= 4/13

User Trludt
by
4.6k points
4 votes

For this case we must find the value of x of the following equation:


- (\frac {6} {5} x + 6) +2 = - \frac {4} {5} (- 5x + 7)

We eliminate the parentheses taking into account that:


- * + = -\\- * - = +\\- \frac {6} {5} x-6 + 2 = 4x- \frac {28} {5}

We simplify the left side:


- \frac {6} {5} x-4 = 4x- \frac {28} {5}

Add
\frac {28} {5} to both sides:


- \frac {6} {5} x-4 + \frac {28} {5} = 4x

Add
\frac {6} {5} x to both sides:


-4+ \frac {28} {5} = 4x + \frac {6} {5} x\\\frac {-20 + 28} {5} =  \frac {20x + 6x} {5}\\8 = 26x\\x = \frac {8} {26}\\x = \frac {4} {13}

Answer:


x = \frac {4} {13}

User Andy Miller
by
5.1k points